Implementasi Standar Kompetensi Lulusan Pendidikan Anak Usia Dini Berdasarkan Permendikdasmen Nomor 10 Tahun 2025 - Catur Ahmad Sofiyanto (Journal of Cultural Relativism (JCR), 2025)
Graduate Competency Standards (SKL) are a fundamental component of the national education system, serving as guidelines for student outcomes at every level of education. The issuance of Ministerial Regulation Number 10 of 2025 marks a significant milestone emphasizing the alignment of SKL from Early Childhood Education (PAUD) to secondary education, although implementation in the field still faces significant challenges. This study aims to explain the concept of SKL based on Permendikdasmen Number 10 of 2025, describe its application at the PAUD level, and analyze the implementation of SKL in PAUD Ana Muslim. This study uses a qualitative approach designed to gain an in-depth understanding of the practices and challenges in implementing SKL. Data collection was conducted through in-depth interviews with principals, teachers, and parents, as well as direct observation at PAUD Ana Muslim. SKL is defined as the minimum qualification for graduates, encompassing aspects of attitude, knowledge, and skills, in line with the vision of the Independent Curriculum. Permendikdasmen Number 10 of 2025 establishes eight dimensions of the graduate profile that children must achieve holistically in PAUD. The implementation of the SKL (Standard Competency Standards) in PAUD (Early Childhood Education) must be based on three main principles: child development-based, enjoyable, and contextual. In the case study at Ana Muslim PAUD (an Islamic-based institution), the SKL was implemented through Islamic character activities that taught simple worship and noble morals, as well as collaboration between children. The main supporting factors for implementation at this institution were the synergistic commitment of teachers, the principal, and parental involvement through Islamic parenting classes. The implementation of the SKL, based on Ministerial Regulation No. 10 of 2025, serves as a crucial guideline that ensures the continuity of children's competency and character development as a whole.